LOS HIDROZOOS (CNIDARIA, HYDROZOA) OF THE CAYERÍA SUR DEL GOLFO DE BATABANÓ, CUB - Castellanos-Iglesias, Susel (2011)
Hydrozoans from shallow waters were collected at 17 stations in July 2004. Stations were located in mangrove forests, seagrass meadows and coral reefs. Two subclases (Anthoathecata and Leptothecata) of hydrozoans were found, including 11 families, 27 genera and 34 species. The collection site, depth, type of substrate, description and pictures are recorded for the fifteenth thecate hydrozoan species. The presence of Hebellopsis communis Calder, 1991a and Antennella siliquos (Hincks, 1877) is confirmed for the Caribbean Sea. The relative abundance is expressed in three categories: abundant, common and rare. Most abundant species were Dynamena crisioides Lamouroux, 1824 in mangrove habitat, Cnydoscyphus marginatus (Allman, 1877) and Sertularella diaphana (Allman, 1885) in coral reefs. Monostaechas quadridens (McCrady, 1859) and Diphasia tropica Nutting, 1904 were rare in general. The most colonized substrates were the submerged red mangrove roots and sponges in the reef. The most colonized hydrozoan was C. marginatus. Specimens were deposited in the collection of marine invertebrates at the National Aquarium of Cuba.